A slice-based algorithm for automatic and feature-preserving hole-filling in a CAD mesh model. Issue 6 (2nd November 2018) - Adhikary, Nepal; Gurumoorthy, B.
ABSTRACT: This paper describes an automatic feature-preserving mesh hole filling algorithm to repair a mesh model, obtained by tessellating a 3D CAD model, with arbitrary holes or gaps. Missing triangles in a mesh model result in such holes or gaps. The proposed algorithm fills the hole while maintaining curvature continuity across the boundaries of the hole. In addition, the algorithm is able to identify missing features such as edges or vertices and reconstruct these. A composite surface patch bound by the boundary of the hole is first constructed and then tessellated to be in conformity with the original mesh to obtain the repaired mesh model. The input mesh remains unchanged in regions away from the holes so any features in the input mesh are preserved. The reconstruction also works in the presence of holes with islands. Algorithm can also fill holes in real world mesh model. Focus is for small holes that result in one missing corner per hole. Results from an implementation tested on various mesh models are presented. GRAPHICAL ABSTRACT: